ANALISIS DEBIT POMPA HIDRAM DENGAN PIPA PARALON SATU OUTPUT, DUA OUTPUT DAN TIGA OUTPUT DENGAN DIAMETER PIPA ¾ INCH - Umar Najib (Wahana Ilmuwan, 2017)
Indonesia is an agricultural country with abundant water. But not all regions in Indonesia can get water easily, especially in hilly areas with springs that are lower than a place to stay. Water is the most important tool in life. Water alone will only flow from a high place to a lower place and certainly an area that has a higher location of water sources will easily meet their daily water needs. The fact has shown that there are many rural areas that have difficulty providing water, both for domestic use and for farming activities due to a water source is lower than a place to stay.At first the hydraulic ram is very popular because of its ease and simplicity in maintenance. But, due to technological progess is very rapidly and also the level of dependence on the higher electrical, hydraulic ram began to be ignored. Along with the increasing attention to equipment that uses renewable energy saving, hydraulic ram began to glance back. From these problems the writer made and did the research about hydraulic ram using the pipe with the diameter of the pump body ¾ inch and output diameter ½ inch. Knowing debit and efficiency of pumps with three variations are made. The trial and the research for the pumps carried out about ten times for each variation about 15 seconds. The pump discharge output Q = 0.007 l/sec. Two output Q1 = 0.005 l/sec and Q2 = 0.002 l/sec. Three output Q1 = 0.003 l/sec, Q2 = 0.002 l/sec and Q3= 0.0018 l/sec. Pump efficiency is 0,16% of the output, two pump output is 0,1143% and 0,0457%, and for the three pump output is 0,0686%, 0,0457% and 0,0411%.